Overview Of The Use Of Modern Contraceptives Among Fertile Age Couples In Ngrandu Village - Rayinda Prasetya Putri; Nurul Fitriyah (International Journal of Health Engineering and Technology, 2026)
The continuous and uncontrolled population growth has a significant impact on demographic aspects and various sectors of life, including the health sector. Family Planning (KB) is one of the government's programs to reduce the birth rate through the use of contraceptives. This study was conducted to obtain an overview of modern contraceptive use among couples of childbearing age (PUS) in Ngrandu Village, reviewed from several demographic characteristics such as age, education level, and type of work. This study used a quantitative descriptive approach with secondary data obtained from the 2024 Self-Awareness Survey conducted by the Ngrandu Health Center. The research sample consisted of women aged 15–49 years who were married. Data analysis was conducted descriptively, and the data were presented in the form of frequency distribution tables and percentages. This study revealed that based on demographic characteristics such as age, education level, and employment status, the participation rate of couples of childbearing age in Ngrandu Village was still relatively low (34.94%). Based on demographic characteristics such as age, education level, and employment status, short-term contraception methods (non-MKJP) were the most widely used contraception methods (55%). Couples of reproductive age who frequently use short-term contraceptive methods (Non-MKJP) are in the 35-39 age group (13.79%) and the 40-44 age group (13.79%), have a high school education or equivalent (27.59%), and are unemployed/housewives (37.93%). Overall, the distribution of contraceptive use among couples of childbearing age in Ngrandu Village shows certain trends in these demographic characteristics. Therefore, it is necessary to develop and optimize reproductive health education and promotion activities, especially those related to contraceptive use among couples of childbearing age.